Degradation mechanisms and lifespan prediction of desert sand dry-mixed mortar under sulfate salt wet-dry cycles - Wenxing Zhu; Luping Wang; Dongge Wu; Shan Wang; Yushan Wang; Haifeng Wang; Rui Wang (Case Studies in Construction Materials)
The protection of the ecological environment and the scarcity of renewable resources are increasingly concerning global issues. To address these challenges, efforts have been made to use desert sand and fly ash in the preparation of building materials. This study attempts to replace river sand with desert sand and cement with fly ash to create an environmentally friendly and economical building material—desert sand dry-mixed mortar (DSDM). Through preliminary mix ratio experiments, five grades of DSDM were developed, and their durability in the saline soil regions of northwest China was studied. The study conducted macro-performance tests on the five strength grades of DSDM after sulfate dry-wet cycles (DWCs), analyzing changes in appearance, mass loss rate, compressive strength loss rate, and flexural strength loss rate. Using SEM, XRD, and NMR testing methods, the degradation mechanisms of the DSDM samples were analyzed. Results indicate that sulfate ions react with hydration products to form ettringite and gypsum, leading to sulfate crystallization. In the initial stages of DWCs, these erosion products fill the pores, increasing density and positively impacting the mortar's performance. However, as the number of cycles increases, excessive accumulation of erosion products leads to further expansion of pores and cracks within the DSDM, increasing the proportion of harmful and more harmful pores, degrading performance, and ultimately causing erosion damage to the mortar. Among the samples, DM5 exhibited the poorest erosion resistance, fracturing after 30 cycles with a mass loss of 43.57 %. DM10 experienced failure after 60 cycles, with its compressive strength retention dropping to 78.86 %. In contrast, DM15, DM20, and DM25 showed the best erosion resistance, with compressive strength retention above 75 % after 120 cycles. Finally, the Wiener random probability distribution was used to predict the remaining life of DSDM samples under different degradation indicators, with flexural strength being the most sensitive indicator. Based on the flexural strength loss rate, the maximum sulfate DWCs for DM5, DM10, DM15, DM20, and DM25 were 132, 118, 78, 52, and 35 cycles, respectively. This study provides a theoretical basis for the promotion and use of DSDM in desert fringe areas.